The Effect of Amifostine on Submandibular Gland Histology after Radiation - Junn, Jacqueline C. (Hindawi Publishing Corporation, 2012)
Background. The purpose of this study was to assess the effects of amifostine on submandibular gland histology in patients receiving chemoradiation therapy. Methods. We conducted a retrospective submandibular gland histologic slide review of HNSCC patients receiving chemoradiation for head and neck squamous cell carcinoma with three different levels of amifostine exposure. We used six scoring parameters: fatty replacement, lobular architecture degeneration, interstitial fibrosis, ductal degeneration, acinar degeneration, and inflammatory component presence. Results. Differences in gender, tumor stage, amifostine dose, age, number of days after neck dissection, and smoking history (pack years) exposure were not significant between the three groups, although there was a difference between groups in the primary subsite (P = 0.006). The nonparametric Cuzick's test for histologic parameters with varied amifostine treatment showed no significance among the three groups. Conclusions. Although patients did not receive a full dose of amifostine due to side effects, varying doses of amifostine had no apparent evident cytoprotective effects in three groups of cancer patients treated with primary chemoradiation.